Knowledge on Childhood Dental Caries Among Parents of Under Five Children in A Community at Biratnagar, Nepal - Pradhan, Sarmila; Khadgi, Deepika; Yengden, Namita; Khadgi, Karishma (Journal of Research and Development, 2021)
Dental caries is a major public health problem globally and is one of the most chronic diseases in children. Children are susceptible to caries as soon as the first teeth appear. Parents are the primary decision-makers in matters of children's healthcare. If the parents are knowledgeable about the child's oral health care then childhood dental caries can be prevented. The objective of this study was to identify the knowledge on childhood dental caries among parents of under five children. A descriptive, cross-sectional study was carried out among parents of under five children in a community of Biratnagar 12. Sample was selected using non probability purposive sampling method and data was collected by face-to-face interview using a self-developed, semi-structured interview guideline. Descriptive statistics i.e. frequency, percentage, mean and standard deviation was used to assess the level of knowledge and inferential statistics i.e chi square was used to find the association between dependent and independent variables. About three fourths (71%) of the parents were of age group 20-30 years and 88% of them were mothers. Most of the parents (90%) were aware that dental caries can occur in under five children and excessive sugar intake was the most common cause as reported by all of them. Only 40% knew that dental caries is transmissible and among them 97.6% responded by sharing of toothbrush. Regarding good brushing habit, most of the parents were aware. Almost all (95%) knew that proper tooth brushing helps to prevent dental caries whereas only 19% were aware about use of fluoridated tooth paste as preventive measures. Meanwhile, only 12% of the parents were aware that first dental visit should be done when first tooth erupts or within 1 year of age More than half (79%) had good knowledge on childhood dental caries but there was no association of knowledge with socio-demographic variables. The study concluded that more than half of the respondents had good knowledge on childhood dental caries and none of the socio-demographic variables were associated with the level of knowledge of parents on dental caries. Despite good knowledge, prevalence of childhood dental caries is high in our society thus reflecting the need to assess the practice of dental care.